Porous dielectric material, preparation method and application

By preparing porous dielectric materials with low dielectric constant, the polymerization phase separation reaction of epoxy monomer, amine source and porogenic agent is adopted, combined with polymerization-induced and non-solvent-induced phase separation, a porous film with a porosity of 60-70%, is solved, and the application of porous dielectric materials in the prior art is insufficient in RF devices, and the reliability and low dielectric constant characteristics of the device are achieved.

CN120383810APending Publication Date: 2025-07-29SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510509479.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

Existing porous dielectric materials cannot meet the application needs of RF devices, especially in terms of low dielectric constant and solvent-free residue, which affects device reliability.

Method used

Porous films were prepared by polymerization and phase separation reactions using epoxy monomers, amine sources and porogenic agents. Combined with polymerization-induced and non-solvent-induced phase separation methods, porous films with a porosity of 60-70%, controlling the size of pore units and forming a 3D through network structure.

Benefits of technology

A porous dielectric material with low dielectric constant is suitable for flexible radio frequency filters, improving device reliability and suitable for portable, wearable electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120383810A_ABST
    Figure CN120383810A_ABST
Patent Text Reader

Abstract

The invention discloses a porous dielectric material, a preparation method and application, the dielectric material is a porous film prepared by polymerization and phase separation reaction of an epoxy monomer, an amine source and a pore-foaming agent, and the porosity of the porous film is 60-70%. The porous film prepared from the raw materials by adopting the preparation method of combining polymeric phase separation and non-solvent induced phase separation is free from the risk of toxic solvent residue, so that the reliability of a device applying the dielectric material is ensured. The size of a basic pore unit can be controlled on the microscale in the polymerization induction process, the formation of an asymmetric structure is facilitated in the non-solvent induction process, so that a 3D through network pore structure is obtained, and under the porosity, the dielectric material has a low dielectric constant, is suitable for a flexible radio frequency filter, and can be applied to the field of flexible radio frequency filters. Therefore, the method can be widely applied to portable and wearable electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of dielectric materials, and relates to a dielectric material, a preparation method and an application thereof. Specifically, it relates to a porous dielectric material with a low dielectric constant, a preparation method and an application thereof. Background Art

[0002] With the rapid development of wireless communication technologies such as 5G, Global Positioning System (GPS), and Internet of Things (IoT), portable and wearable electronic devices have been widely used, thus posing higher requirements for the high integration and flexibility of wireless communication components. Among them, radio frequency (RF) devices have gradually become important components in wireless communication systems due to their powerful function of transmitting modulated signals. In RF devices, dielectric materials, as key substrate materials, play multiple important roles: First, dielectric materials can be used to isolate and protect circuit elements in RF devices; Second, dielectric materials can be used to reduce filtering and parasitic losses, and play an important role in signal integrity, noise reduction effect, and ensuring power efficiency. With the miniaturization of RF devices and the increase in operating frequency, low dielectric constant (k) dielectric materials have become increasingly important because they can reduce the capacitive coupling effect between wires, prevent signal delay, reduce conductor losses, and reduce the size of filters.

[0003] To achieve a dielectric constant (Dk) lower than 2.0, the commonly used method is to introduce air (whose dielectric constant Dk is 1) into the dielectric material. To introduce air, a pore structure needs to be formed in the polymer dielectric. Currently, there are mainly the following two ways to form pores in polymer dielectrics: (1) The intrinsic method (self-organization), forming an internal pore structure during the polymer synthesis process; (2) The template method (post-forming), introducing a pore structure after the polymer synthesis. In contrast, the template method has higher flexibility in material selection and precise control of pore size, and mainly includes the hard template method and the foaming process. However, the hard template method has problems such as the need to remove the etchant, poor pore connectivity, and limited reduction of Dk, and the foaming process has problems such as low effective porosity and a wide range of cell size distributions. To solve the above technical problems, the phase separation technology that forms a porous structure by regulating the interaction between the solvent and the non-solvent has attracted much attention in recent years. This method can create a pore structure with uniform distribution and adjustable pore size from basic monomers. However, the dielectric materials prepared by the existing phase separation technology still cannot fully meet their applications in RF devices and wireless communication. For example, there is a risk of solvent residue, resulting in insufficient device reliability.

[0004] In view of this, it is necessary to further improve the dielectric materials of the existing technology. Summary of the Invention

[0005] To this end, the technical problem to be solved by the present invention is that the existing porous dielectric materials cannot meet the application requirements of radio frequency devices, and thus a porous dielectric material with optimized reaction raw materials, reaction conditions, etc., its preparation method and application are proposed.

[0006] To solve the above technical problems, the technical solution of the present invention is as follows:

[0007] The first aspect of the present invention provides a porous dielectric material, which is a porous film prepared by the polymerization and phase separation reaction of an epoxy monomer, an amine source and a pore-forming agent, and the porosity of the porous film is 60-70%.

[0008] Preferably, the dielectric constant of the porous dielectric material is 1.82-1.9.

[0009] Preferably, the epoxy monomer includes at least one of bisphenol A diglycidyl ether and bisphenol A propoxylated diglycidyl ether; the amine source includes at least one of piperazine and 1-(2-aminoethyl)piperazine; the pore-forming agent is polyethylene glycol.

[0010] Preferably, the average molecular weight of the polyethylene glycol is not more than 1000.

[0011] The second aspect of the present invention provides a method for preparing the porous dielectric material, which is characterized by including the following steps:

[0012] S1. By mass, 100 parts of the pore-forming agent polyethylene glycol is mixed with 6-9 parts of ethanol to obtain a premixed solution;

[0013] S2. 4.8-7.3 parts of an amine source is added to the premixed solution, stirred for 30-60 min under heating conditions, and then cooled to room temperature to obtain a precursor solution;

[0014] S3. 23.3-35 parts of an epoxy monomer is added to the precursor solution, and stirring is continued for 15-16 min to obtain a prepolymer solution;

[0015] S4. The prepolymer solution is coated on the surface of a base layer to form a prepolymer coating;

[0016] S5. The base coated with the prepolymer coating is heated and cured to obtain a cured composite material;

[0017] S6. After the cured composite material is cooled, it is treated in a warm water bath for 12-24 h to remove unreacted polyethylene glycol to obtain a porous dielectric film.

[0018] Preferably, in step S2, by mass, the amine source includes 4.2 - 6.3 parts of piperazine and 0.6 - 1 part of 1-(2-aminoethyl)piperazine, and the temperature during the heating process is 40 - 60°C; in step S5, the temperature increase and curing are carried out at 80 - 140°C for 3 - 6 h; in step S6, the temperature of the warm water bath is 50 - 80°C.

[0019] Preferably, by mass, the epoxy monomer includes 16.4 - 24.7 parts of bisphenol A diglycidyl ether and 6.9 - 10.3 parts of bisphenol A propoxyl diglycidyl ether; the base layer includes a polytetrafluoroethylene layer and a non-woven fabric layer stacked from bottom to top, and the prepolymer solution is coated on the non-woven fabric layer.

[0020] The third aspect of the present invention provides an application of the porous dielectric material in a flexible radio frequency filter.

[0021] Preferably, the flexible radio frequency filter is fabricated by the following method:

[0022] a. Magnetron sputtering is used to prepare a Ti / Cu seed layer on the surface of the porous thin film;

[0023] b. A copper conductive layer is electroplated on the surface of the seed layer to obtain a conductive thin film, and the conductive thin film is washed and dried;

[0024] c. A mask layer is attached to the surface of the conductive thin film without the electroplated copper layer, and an Ag pattern is sputtered to obtain the flexible radio frequency filter.

[0025] Preferably, the thickness of the Ti / Cu seed layer is 50 - 500 nm; the thickness of the copper conductive layer is 13 - 17 μm; during the electroplating of the copper conductive layer, the current density is 1 - 2 A / dm 2 .

[0026] The above technical solutions of the present invention have the following advantages compared with the prior art:

[0027] The porous dielectric material provided by the present invention is specifically a porous thin film prepared by the polymerization and phase separation reaction of an epoxy monomer, an amine source, and a pore-forming agent. The porosity of the porous thin film is 60 - 70%. The porous thin film prepared by the above raw materials and the preparation method combining polymerization-induced phase separation and non-solvent-induced phase separation has no risk of toxic solvent residues, thus ensuring the reliability of the devices using this dielectric material. The polymerization-induced process can control the size of the basic pore units at the microscale, and the non-solvent-induced process helps to form an asymmetric structure, thereby obtaining a 3D interconnected network pore structure. At the above porosity, this dielectric material has a low dielectric constant, is suitable for flexible radio frequency filters, and can further be used in portable and wearable electronic devices. Description of the Drawings

[0028] To make the content of the present invention more easily understood clearly, the following further details the present invention according to specific embodiments of the present invention and in conjunction with the accompanying drawings, wherein

[0029] Figure 1 is the synthesis route diagram of the porous dielectric material provided by the embodiment of the present invention;

[0030] Figure 2 (a)-(d) are scanning electron microscope images of the porous dielectric material provided by Embodiment 1 of the present invention under different PEG mass fractions;

[0031] Figure 3 (a)-(d) are physical images of the porous dielectric material provided by Embodiment 1 of the present invention under different PEG mass fractions;

[0032] Figure 4 (a)-(d) are scanning electron microscope images of the porous dielectric material provided by Embodiment 1 of the present invention under different water bath temperatures;

[0033] Figure 5 is the three-dimensional response curve graph of the dielectric constant - PEG mass fraction - etching temperature of the porous dielectric material provided by Embodiment 1 of the present invention;

[0034] Figure 6 is the function relationship graph of the dielectric constant and the PEG mass fraction of the porous dielectric material provided by Embodiment 1 of the present invention at high frequencies;

[0035] Figure 7 is the physical image of the porous dielectric material provided by Embodiment 1 of the present invention;

[0036] Figure 8 is the hydrophobicity test result of the porous dielectric material provided by Embodiment 1 of the present invention under different PEG mass fractions;

[0037] Figure 9 is the schematic cross-sectional view of the flexible filter;

[0038] Figure 10 is the test curve graph of the simulated S parameters and the measured S parameters of the flexible filter. Specific Embodiments

[0039] Embodiment 1

[0040] This embodiment provides a porous dielectric material, which is an epoxy resin-based porous film prepared by the polymerization and phase separation reaction of an epoxy monomer, an amine source, and a pore-forming agent. The porosity of the porous film is 60 - 70%, the thickness is not less than 0.2 μm, and its dielectric constant is 1.82 - 1.9, which is a low-k dielectric material.

[0041] Among them, the epoxy monomer includes at least one of bisphenol A diglycidyl ether (BADGE) and bisphenol A propoxylated diglycidyl ether (BAPDGE); the amine source includes at least one of piperazine (PIP) and 1-(2-aminoethyl)piperazine (AEP); the pore former is polyethylene glycol (PEG), and the average molecular weight of polyethylene glycol is not greater than 1000, and PEG is preferably used in this embodiment. 400 .

[0042] The porous dielectric material provided in this embodiment is prepared by the following steps:

[0043] S1. By mass, mix 100 parts of the pore former PEG 400 with 7.56 parts of ethanol to obtain a premixed solution.

[0044] S2. Add the amine source: 5.29 parts of PIP and 0.76 parts of AEP to the premixed solution, stir at 60 °C for 30 min, and then cool to room temperature to obtain a precursor solution. Among them, PIP acts as a curing crosslinking agent, and AEP acts as an auxiliary curing agent to accelerate the ring-opening reaction.

[0045] S3. Add 20.57 parts of BADGE and 8.63 parts of BAPDGE to the precursor solution, and continue to stir for 15 min to ensure sufficient pre-reaction between the glycidyl ether groups of the epoxy monomer and the amine curing agent to obtain a prepolymer solution.

[0046] S4. Coating the prepolymer solution on the surface of the base layer to form a prepolymer coating. The base layer includes a polytetrafluoroethylene (PTFE) layer and a non-woven fabric layer stacked from bottom to top. The prepolymer solution is coated on the non-woven fabric layer, where PTFE serves as a reinforcing skeleton.

[0047] S5. Place the base layer coated with the prepolymer solution in an oven for high-temperature curing. The curing temperature is 120 °C and the curing time is 6 h to obtain a cured composite material.

[0048] S6. Cool the cured composite material to room temperature, and then perform a water bath treatment at 50 °C for 24 h to remove the unreacted non-reactive PEG 400 , thereby forming through channels to obtain a porous dielectric film attached with a base layer.

[0049] The porous dielectric material provided in this embodiment is prepared by the above raw materials and a preparation method combining polymerization-induced phase separation and non-solvent-induced phase separation. The resulting porous film has no risk of solvent residue, ensuring the reliability of the devices using this dielectric material. The polymerization-induced process can control the size of the basic pore units at the microscale, while the non-solvent-induced process helps to form an asymmetric structure, thus obtaining a 3D interconnected network void structure. At the above porosity, this dielectric material has a low dielectric constant (not greater than 1.9), is suitable for flexible RF filters, and further suitable for portable and wearable electronic devices.

[0050] The porous dielectric material provided in this embodiment optimizes the mechanical properties of the porous dielectric film by using a compounding method of BADGE and BAPDGE epoxy monomers. By utilizing the rigid skeleton of BADGE and the flexible propoxy chain segments of BAPDGE, and since epoxy resins are widely used in the electronics industry, using the above epoxy resins as polymerization monomers is more suitable for industrialization. By regulating the polymerization process with piperazine (PIP) and 1-(2-aminoethyl)piperazine (AEP) dual amine curing agents, a polyhydroxyaminoether (PHAE) network with adjustable chain rigidity-crosslinking degree is formed (as Figure 1 shown), and PEG 400 acts both as a pore-forming agent to form pores through phase separation and can reduce the polarity of the curing system, enhance the crosslinking rate, reduce hydroxyl residues, and PEG 400 has excellent viscosity parameters, making the film-forming property of the slurry optimal during the preparation of the porous dielectric material. Immersing the PHAE / PEG composite material in water selectively etches the hydrophilic PEG phase domain to form a 3D interconnected network pore structure. The three-dimensional fiber network of the non-woven fabric in the base layer not only provides mechanical support but also acts as a capillary channel to promote the mass transfer efficiency of PEG 400 dissolution.

[0051] The preparation process provided in this embodiment also has the advantages of mild reaction conditions, environmental friendliness, high reaction efficiency, and can complete phase separation and crosslinking in one step.

[0052] This embodiment also provides an application of the above porous dielectric material in a flexible filter. The flexible filter is prepared by the following method:

[0053] a. Remove the base layer, and deposit a Ti / Cu seed layer on the back of the porous dielectric film (PHAE) by magnetron sputtering. The thickness of the Ti / Cu seed layer is 50 nm.

[0054] b. Electroplate a copper conductive layer on the surface of the Ti / Cu seed layer. During the electroplating process, the current density is 2 A / dm 2 , and the thickness of the copper conductive layer is 15 μm to obtain a conductive film. Wash the conductive film with deionized water and dry the film with a nitrogen gun.

[0055] c. Attach a hard mask (chromium / quartz material, pattern accuracy ±2 μm) to the front side of the conductive thin film (the surface without the electroplated copper layer), and sputter to prepare an Ag pattern: The 1-μm-thick Ag pattern is sputtered 2 times at a sputtering frequency of 860 s / time to form an Ag pattern with a thickness of 2 μm. The cooling interval between the two sputterings is 30 min to avoid the desorption of the Ag layer caused by thermal stress, that is, a flexible RF filter is obtained and stored in a dry environment.

[0056] Example 2

[0057] This example provides a porous dielectric material, which is prepared by the following steps:

[0058] S1. By mass, mix 100 parts of the pore-forming agent PEG 400 with 6 parts of ethanol to obtain a premixed solution.

[0059] S2. Add amine sources: 4.2 parts of PIP and 0.6 parts of AEP to the premixed solution, stir at 40 °C for 60 min, and then cool to room temperature to obtain a precursor solution. Among them, PIP acts as a curing crosslinking agent, and AEP acts as an auxiliary curing agent to accelerate the ring-opening reaction.

[0060] S3. Add 16.4 parts of BADGE and 6.9 parts of BAPDGE to the precursor solution, and continue to stir for 16 min to ensure the sufficient pre-reaction of the glycidyl ether groups of the epoxy monomers with the amine curing agent to obtain a prepolymer solution.

[0061] S4. Coating the prepolymer solution on the surface of the base layer to form a prepolymer coating. The base layer includes a polytetrafluoroethylene (PTFE) layer and a non-woven fabric layer stacked from bottom to top. The prepolymer solution is coated on the non-woven fabric layer, where PTFE serves as a reinforcing framework.

[0062] S5. Place the base layer coated with the prepolymer solution in an oven for high-temperature curing. The curing temperature is 80 °C, and the curing time is 5 h to obtain a cured composite material.

[0063] S6. Cool the cured composite material to room temperature, and then perform a water bath treatment at 80 °C for 12 h to remove the unreacted non-reactive PEG 400 , thereby forming through holes to obtain a porous dielectric film attached with a base layer.

[0064] This example also provides an application of the above porous dielectric material in a flexible filter. The flexible filter is prepared by the following method:

[0065] a. Remove the base layer, and deposit a Ti / Cu seed layer on the back of the porous dielectric thin film (PHAE) by magnetron sputtering. The thickness of the Ti / Cu seed layer is 50 nm.

[0066] b. Electroplate a copper conductive layer on the surface of the Ti / Cu seed layer. During the electroplating process, the current density is 1 A / dm 2 , and the thickness of the copper conductive layer is 13 μm to obtain a conductive thin film. Wash the conductive thin film with deionized water and dry the film with a nitrogen gun.

[0067] c. Attach a hard mask (made of chromium / quartz, with a pattern accuracy of ±2 μm) to the front side of the conductive thin film (the surface without the electroplated copper layer), and sputter to prepare an Ag pattern: The 1-μm-thick Ag pattern is sputtered 2 times at a sputtering frequency of 860 s / time to form an Ag pattern with a thickness of 2 μm. Cool for 30 min between the two sputterings to avoid the desorption of the Ag layer caused by thermal stress, that is, a flexible RF filter is obtained, and it is stored in a dry environment.

[0068] Example 3

[0069] This example provides a porous dielectric material, which is prepared by the following steps:

[0070] S1. By mass, mix 100 parts of porogen PEG 400 with 9 parts of ethanol to obtain a premixed solution.

[0071] S2. Add amine sources: 6.3 parts of PIP and 1 part of AEP to the premixed solution, stir at 50 °C for 45 min, and then cool to room temperature to obtain a precursor solution. Among them, PIP acts as a curing crosslinking agent, and AEP acts as an auxiliary curing agent to accelerate the ring-opening reaction.

[0072] S3. Add 24.7 parts of BADGE and 10.3 parts of BAPDGE to the precursor solution, and continue to stir for 15.5 min to ensure the sufficient pre-reaction of the glycidyl ether groups of the epoxy monomers with the amine curing agent to obtain a prepolymer solution.

[0073] S4. Coating the prepolymer solution on the surface of the base layer to form a prepolymer coating. The base layer includes a polytetrafluoroethylene (PTFE) layer and a non-woven fabric layer stacked from bottom to top. The prepolymer solution is coated on the non-woven fabric layer, where PTFE serves as a reinforcing skeleton.

[0074] S5. Place the base layer coated with the prepolymer solution in an oven for high-temperature curing. The curing temperature is 100 °C, and the curing time is 4.5 h to obtain a cured composite material.

[0075] S6. Cool the cured composite material to room temperature, and then perform a water bath treatment at 60 °C for 15 h to remove the unreacted non-reactive PEG400 , thereby forming a through-hole channel to obtain a porous dielectric film with a base layer attached thereto.

[0076] This embodiment also provides an application of the above-mentioned porous dielectric material in a flexible filter, and the flexible filter is prepared by the following method:

[0077] a. Remove the base layer, and deposit a Ti / Cu seed layer on the back of the porous dielectric film (PHAE) by magnetron sputtering. The thickness of the Ti / Cu seed layer is 300 nm.

[0078] b. Electroplate a copper conductive layer on the surface of the Ti / Cu seed layer. During the electroplating process, the current density is 1.5 A / dm 2 , and the thickness of the copper conductive layer is 17 μm to obtain a conductive film. Wash the conductive film with deionized water and dry the film with a nitrogen gun.

[0079] c. Attach a hard mask (made of chromium / quartz, with a pattern accuracy of ±2 μm) to the front side (the surface without the electroplated copper layer) of the conductive film, and sputter to prepare an Ag pattern: The 1-μm-thick Ag pattern is sputtered 2 times at a sputtering frequency of 860 s / time to form an Ag pattern with a thickness of 2 μm. Cool for 30 min between the two sputterings to avoid the desorption of the Ag layer caused by thermal stress, that is, a flexible RF filter is obtained and stored in a dry environment.

[0080] Experimental Example

[0081] 1. Test on the effect of polymerization-induced phase separation (PIPS):

[0082] Test the influence of different PEG 400 contents on the epoxy structure under a fixed amine source ratio. Prepare a porous dielectric material by the preparation method provided in Example 1. Among them, the mass fractions of PEG 400 are 40%, 50%, 60%, and 70% respectively. The obtained PHAE-PEG composite systems are: PHAE-PEG40, PHAE-PEG50, PHAE-PEG60, and PHAE-PEG70. Test the scanning electron microscope images (SEM) of the prepared porous dielectric materials. The test results are as Figure 2 (a)-(d) shown. It can be seen from the figure that as the mass fraction of PEG 400 increases, the size of the PEG domain in the PHAE / PEG composite material increases, resulting in an increase in porosity.

[0083] The photo of the porous dielectric film is as Figure 3(a)-(d) As shown; it can be seen from the figure that the opacity of the thin film is consistent with the cross-sectional SEM image. It can be seen from the figure that when the pores are small, the porous dielectric thin film has high transparency. Therefore, by controlling the polymer chemistry and the ratio of the polymer to the additive, it is possible to have an impact at the micro and meso scales. Therefore, polymerization-induced phase separation mainly affects the size of the basic pore units.

[0084] 2. Test on the role of non-solvent induced phase separation (NIPS):

[0085] PEG 400 The displacement with water (corresponding to the removal of the polymer-poor phase region) is a kinetically controlled process, similar to the traditional non-solvent induced phase separation mechanism, but there is still a lack of systematic discussion on its regulation mechanism for the final multi-scale structure. In the PHAE / PEG composite system, PEG can be regarded as the solvent phase. When the composite system comes into contact with a poor solvent (non-solvent) that can be miscible with the PEG domain, with the dynamic exchange of PEG and water, the precipitation phase separation of the PHAE matrix is triggered.

[0086] Test the interface SEM images of the porous dielectric materials obtained at different etching temperatures. When the etching temperatures are 20 °C, 40 °C, 60 °C, and 80 °C respectively, the obtained porous dielectric thin films are: PHAE-20, PHAE-40, PHAE-60, PHAE-80. The test results are as Figure 4 (a)-(d) As shown. It can be seen from the figure that as the temperature increases, the cross-sectional SEM morphology shows a significant transformation from a closed-cell sponge-like structure to an open finger-like pore channel. This is because as the temperature increases, the viscosity of the composite system decreases, enhancing the mobility of the polymer segments, and thus accelerating the dynamic displacement rate of PEG / water. The precise construction of the microstructure essentially depends on the coordinated regulation of core parameters such as the phase separation rate, solution concentration, and temperature gradient.

[0087] In summary, in the mixed phase separation process, polymerization-induced phase separation (PIPS) is mainly used to regulate the size of micro / meso-scale primary pore units (intrinsic pore construction), endowing the material with inherent structural designability. Non-solvent induced phase separation (NIPS) dominates the formation of an asymmetric structure (post-processing pore formation mechanism), determining the overall interface morphology of the thin film. The above two cross-scale collaborative strategies have both cost advantages and material universality advantages, achieving the effect of precisely controlling the pore size at different scales through dual kinetic paths, providing a structured general solution for the development of multifunctional materials.

[0088] 3. Dielectric constant test:

[0089] The dielectric properties of the dielectric material provided in Example 1 were tested by broadband scanning. In the frequency range of 100 Hz - 10 MHz, the thin-film capacitance (C) and loss factor (tanδ) were measured with a parallel-plate electrode fixture, and the dielectric constant (Dk) and dissipation factor (Df) were obtained by calculation.

[0090] As Figure 5 shown, by constructing a three-dimensional response curve of dielectric constant (Dk) - PEG mass fraction - etching temperature, the influence of phase separation kinetics on the porous structure of the PHAE-PEG composite was revealed. As the PEG mass fraction increased, the dielectric constant (Dk) decreased. Among them, the PHAE-PEG70 system exhibited the lowest Dk value (2.68) at 10 MHz, which was attributed to its highly porous structure. At the same time, there were significant dielectric differences between the sponge-like pores and finger-like pores caused by different etching temperatures: when the PEG content was 70 wt.%, the Dk value of the sponge-like pores was lower than that of the finger-like pores. Mechanism studies showed that the difference in pore morphology led to the reconstruction of the electric field distribution: the high connectivity of the finger-like pores promoted the formation of a honeycomb-like polymer network skeleton, triggering the local concentration effect of the electric field.

[0091] In addition, the function relationship between the dielectric constant of the PHAE thin film and the PEG mass fraction at high frequency (5 GHz) was also measured by the resonant cavity method. The test results are as Figure 6 shown. The test results were consistent with the low-frequency test results, confirming the consistency of the dielectric behavior of this porous dielectric material at different frequencies. By optimizing the monomer ratio, polymerization, and etching conditions, a PHAE thin film with a sponge-like porous structure body combined with a pore-free ultra-smooth skin layer was obtained in this application. An ultra-low dielectric property of Dk = 1.86 ± 0.04 and Df = 0.0050 ± 0.0003 at 5 GHz was achieved. The decisive role of the synergistic effect of porosity and morphology on the dielectric properties of low-k materials was revealed, and a lower Dk value could be obtained with a sponge-like structure.

[0092] In addition, as Figures 7-8 shown, the PHAE thin film provided in this application also has excellent flexibility and good hydrophobicity. Its preparation process is environmentally friendly and mild in conditions, without toxic solvents or catalysts, and has strong application potential in flexible radio frequency devices.

[0093] 4. Flexible filter performance test:

[0094] To further verify the dielectric properties of the porous dielectric material provided in this application, the porous dielectric material provided in Example 1 was used as the flexible substrate of a radio frequency device, and a low-pass filter with a specific size was designed. The size of the low-pass filter is shown in Table 1 below:

[0095] Table 1

[0096]

[0097] The porous dielectric material provided in Embodiment 1 of the present application has excellent dielectric properties with Dk = 1.86 ± 0.04 at 5 GHz. A silver circuit structure (2 μm thick) is constructed on the front of the porous dielectric material by magnetron sputtering, and a copper layer with a thickness of 15 μm is deposited on the back of the porous dielectric material as a ground plane. Figure 9 A cross-sectional view of the device is shown, and it can be seen that the porous dielectric material maintains good structural integrity during the manufacturing process.

[0098] The simulation and measured S-parameter test diagrams of the low-pass filter are as Figure 10 shown. Specifically, the measured 3-dB passband frequency range is from 0 to 8.5 GHz. The corresponding maximum in-band insertion loss measured is 1.2 dB, and the return loss is better than 16.5 dB. In addition, TZ1 helps to achieve better frequency selectivity, and the out-of-band rejection depth reaches 28 dB. The above results together verify the feasibility of the porous dielectric material in the preparation of low-pass filters.

[0099] Obviously, the above embodiments are merely examples for clear illustration and not limitations on the implementation manners. For those of ordinary skill in the art, other different forms of changes or variations can be made based on the above description. It is not necessary and impossible to enumerate all the implementation manners here. And the obvious changes or variations derived therefrom are still within the protection scope of the present invention.

Claims

1. A porous dielectric material, characterized in that, The porous dielectric material is a porous film prepared by the polymerization and phase separation reaction of an epoxy monomer, an amine source, and a pore-forming agent. The porosity of the porous film is 60-70%.

2. The porous dielectric material according to claim 1, characterized in that, The dielectric constant of the porous dielectric material is 1.82-1.

9.

3. The porous dielectric material according to claim 1 or 2, characterized in that, The epoxy monomer includes at least one of bisphenol A diglycidyl ether and bisphenol A propoxydiglycidyl ether; the amine source includes at least one of piperazine and 1-(2-aminoethyl)piperazine; the pore-forming agent is polyethylene glycol.

4. The porous dielectric material according to claim 3, characterized in that, The average molecular weight of the polyethylene glycol is not greater than 1000.

5. A method for preparing a porous dielectric material as described in any one of claims 1-5, characterized in that, It includes the following steps: S1. Mix 100 parts by mass of the pore-forming agent polyethylene glycol with 6-9 parts of ethanol to obtain a premixed solution. S2. Add 4.8-7.3 parts of the amine source to the premixed solution, stir for 30-60 min under heating conditions, and then cool to room temperature to obtain a precursor solution. S3. Add 23.3-35 parts of the epoxy monomer to the precursor solution and continue stirring for 15-16 min to obtain a prepolymer solution. S4. Coat the prepolymer solution on the surface of the base layer to form a prepolymer coating. S5. Heat and cure the substrate coated with the prepolymer coating to obtain a cured composite material. S6. After cooling the cured composite material, perform a warm water bath treatment for 12-24 h to remove the unreacted polyethylene glycol to obtain a porous dielectric film.

6. The preparation method according to claim 5, wherein In step S2, by weight, the amine source includes 4.2-6.3 parts of piperazine and 0.6-1 part of 1-(2-aminoethyl)piperazine, and the temperature during the heating process is 40-60°C; in step S5, the heat-up curing is carried out at 80-140°C for 3-6 h; in step S6, the temperature of the warm water bath is 50-80°C.

7. The preparation method according to claim 6, characterized in that, By weight, the epoxy monomer includes 16.4-24.7 parts of bisphenol A diglycidyl ether and 6.9-10.3 parts of bisphenol A propoxydiglycidyl ether; the base layer includes a polytetrafluoroethylene layer and a non-woven fabric layer stacked from bottom to top, and the prepolymer solution is coated on the non-woven fabric layer.

8. The application of the porous dielectric material according to any one of claims 1-4 in a flexible radio frequency filter.

9. The application according to claim 8, wherein The flexible radio frequency filter is fabricated by the following method: a. Magnetron sputter a Ti / Cu seed layer on the surface of the porous film. b. Electroplate a copper conductive layer on the surface of the seed layer to obtain a conductive film, and wash and dry the conductive film. c. Attach a mask layer to the surface of the conductive film where the copper layer is not electroplated, and sputter an Ag pattern to obtain the flexible radio frequency filter.

10. The application according to claim 9, wherein, The thickness of the Ti / Cu seed layer is 50 - 500 nm; the thickness of the copper conductive layer is 13 - 17 μm; during the process of electroplating the copper conductive layer, the current density is 1 - 2 A / dm 2 .